Dynamics Characteristic Analysis of a Spur Gear based on Measured Tooth Surface Error - Chen Siyu; Bai Fan; Tang Jinyuan (Jixie chuandong)
Gear tooth surface error is main excitation source of vibration and noise in gear system. In order to study the influence of tooth surface error on gear system,the static transmission error is calculated for gear system with measured errors such as profile deviation,run out and pitch errors by tooth contact analysis method.In this work,a differential equation of vibration for gear system with time-varying meshing stiffness,blackness,meshing damping and static transmission error is established on the basis of previous research for gear transmission system. The dynamic characteristic of gear system is obtained by numerical analysis method. The results show that static transmission error with measured errors has more actual components. The profile deviation has higher influence on gear system at low rotation speed,and run out and pitch error have higher influence on gear system at high rotation speed.